PENDIDIKAN MULTIKULTULAR DI INDONESIA: URGENSI SEBAGAI RESOLUSI KONFLIK - Dias Syahrul Riyadi; Arif Rahman; Tanti Julianti; Alfina Duta Ananda; Akhmad Baharudin (TA'LIM : Jurnal Studi Pendidikan Islam, 2022)
This research focuses on a pluralistic Indonesian nation that has ethnic, racial, social, semantic and cultural diversity, conflicts often arise in this country, a multicultural approach as conflict resolution, with this multicultural education can change people's perspectives, and live a pluralistic life, maintain integration nation and identity instead of creating conflict between groups, the purpose of the research is to know in detail about multicultural education in depth, secondly to examine in detail multiculturalism as conflict resolution, especially in Indonesia, thirdly to understand the urgency of multicultural education in Indonesia, the method used by researchers is library study method, library research, library study, data analysis. In using this method, researchers get a lot of information and data from various sources such as books, journals, etc. Data analysis method is used to answer all the existing problems. The results of this study indicate that multiculturalism is very important to maintain the integrity, strength, unity and progress of the country and the world.